Teachers’ Role in Developing Entrepreneurial Competencies of Muhammadiyah Vocational School Students in Ambon via Innovative Flipped classroom Approach - Aminah Rehalat; Zuhria Nurul ‘Ainy (STKIP Taman Siswa Bima, 2025)
This study aims to analyze the role of teachers in developing students’ entrepreneurial competence through the application of an innovative flipped classroom learning model at SMK Muhammadiyah Ambon. The study was conducted using a qualitative descriptive approach, with data obtained from classroom observations, interviews with entrepreneurship subject teachers, and documentation of students’ activities. The results show that teachers play a crucial role in preparing digital learning materials, such as videos and modules, which students study before face-to-face sessions. During classroom learning, teachers facilitate discussions, guide group work, and encourage students to present and simulate business ideas. The findings highlight that teachers act as facilitators, motivators, and mentors who foster creativity, critical thinking, and confidence in expressing entrepreneurial concepts. The study concludes that the implementation of the flipped classroom model is effective in strengthening entrepreneurial competence in vocational high schools and emphasizes the importance of teacher innovation in 21st-century learning.